‘Yellow is good for you’: Consumer perception and acceptability of fortified and biofortified cassava products - Bechoff, Aurélie (PLoS One, 2018)
Vitamin A, an essential micronutrient for health, can be obtained from various food sources including cassava products made from either traditional white cassava varieties fortified with red palm oil containing provitamin A, or new high provitamin A biofortified yellow cassava varieties. Both products have a similar yellow appearance due to the coloured pigmentation of provitamin A. Using a range of methods to provide a comprehensive understanding of sensory acceptability (blind triangle test, sensory profiling, hedonic preference that included Check-all-that-applies and Just-about-right tests), we tested the acceptability and nutritional perception of traditional West-African food dough-like products (eba and fufu) made from biofortified, fortified, or control products made with non-fortified white cassava (n = 7) at three suburban locations near Ibadan, Nigeria on a total of 122 consumers. Biofortified, fortified, and control products could be differentiated blindly confirming that products clearly differed with respect to other sensory characteristics than appearance. Overall biofortified products were better accepted than control and fortified ones. Three classes of consumer preference were identified based on the dislike for control and fortified products, which indicated that acceptance of biofortified products was not a hindrance. On the contrary the traditional fortified product had poorer acceptance and this was due to its less desirable sensory characteristics as demonstrated by Just-about-right Penalty analysis. A majority of consumers (85%) had previous knowledge of biofortified cassava. Consumers associated ‘yellow colour’ with ‘good for eyesight’, ‘good for children’s health’ and ‘new’. More nutritional benefits were attributed to biofortified than fortified products although they had similar provitamin A contents and this demonstrates a bias. We suggest that nutrition promotion campaigns to improve the vitamin A status should also encompass all natural sources of provitamin A, including biofortified and traditional fortified products.